Risk of Redislocation After Primary Patellar Dislocation: A Clinical Prediction Model Based on Magnetic Resonance Imaging Variables. Issue 14 (December 2018) - Arendt, Elizabeth A.; Askenberger, Marie; Agel, Julie; Tompkins, Marc A.
Background: First-time lateral patellar dislocations have historically been treated with a nonoperative approach; a clinical tool to predict patients who are most likely to redislocate may have clinical utility. Purpose: (1) To determine if there are discriminating factors present between patients who redislocated their patellas and those who did not after a first-time lateral patellar dislocation and (2) to use this information to develop a model that can predict the recurrence risk of lateral patellar dislocation in this population. Study Design: Case-control study; Level of evidence, 3. Methods: The study population included those with first-time lateral patellar dislocation, magnetic resonance imaging within 6 weeks, and 2-year minimum follow-up. Cohort A was from a prospective study with 2-year follow-up. Cohort B was a prospectively identified cohort with retrospective chart review. Follow-up was obtained clinically or via mail for patients without 2-year clinical follow-up. Results: Sixty-one patients (42%) out of 145 with primary lateral patellar dislocation had recurrent dislocation within 2 years. Stepwise logistic regression analysis demonstrated that skeletal immaturity (odds ratio, 4.05; 95% CI, 1.86-8.82; P = .0004), sulcus angle (odds ratio, 4.87; 95% CI, 2.01-11.80; P = .0005), and Insall-Salvati ratio (odds ratio, 3.0; 95% CI, 1.34-6.70; P = .0074) were significant predictors of redislocation. Receiver operator characteristic curves defined the cut points to be sulcus angle ≥154° and Insall-Salvati ratio ≥1.3. The probability of redislocation based on the presence of factors was 5.8% with no factors present and 22.7% with any 1 factor present, increasing to 78.5% if all 3 factors were present. Conclusion: This model demonstrates a high risk of lateral patellar redislocation when a patient presents with skeletal immaturity as well as magnetic resonance measurements of sulcus angle ≥154° and patellar height as measured by Insall-Salvati ratio ≥1.3. A patient will have a low risk of lateral patellar redislocation with the inverse findings.